The Effects of Microplastics and Heavy Metals Individually and in Combination on the Growth of Water Spinach (Ipomoea aquatic) and Rhizosphere Microorganisms - Jing-Yi Wang; Meng Wang; Jian-Wei Shi; B. Larry Li; Ling Liu; Peng-Fei Duan; Zhao-Jin Chen (Agronomy)
Microplastics (MPs) and heavy metals are commonly present in soil at significant concentrations and can interact in complex ways that pose serious threats to environmental and ecological systems. The effects of combined contamination by different types of heavy metals and microplastics on plants, as well as on soil microbial communities and their functions, remain largely unexplored. In this study, a series of pot experiments was conducted to investigate the effects of composite contamination involving two heavy metals (Cd and Pb) and two types of microplastics polylactic acid (PLA) and polybutylene succinate (PBS) at varying concentrations (0.1% and 0.5%, w/w). The impacts on water spinach (Ipomoea aquatica) growth and heavy metal accumulation were evaluated, and the rhizosphere bacterial and fungal community structure and diversity were analyzed using high-throughput sequencing. The presence of Cd, Pb, and microplastics significantly inhibited the growth of water spinach, reducing both its length and biomass. Under combined microplastic–heavy metal contamination, phytotoxicity increased with rising concentrations of PLA and PBS. Microplastics were found to alter the mobility and availability of heavy metals, thereby reducing their accumulation in plant tissues and decreasing the levels of available potassium and phosphorus in the soil. Furthermore, microplastic–heavy metal interactions significantly influenced the composition and diversity of soil microbial communities, leading to an increased abundance of heavy-metal-tolerant and potential plastic-degrading microorganisms. A strong correlation was observed between microbial community structure (both bacterial and fungal), soil physicochemical properties, and plant growth. Functional predictions using PICRUSt2 suggested that the type and concentration of microplastics significantly affected rhizosphere microorganisms’ metabolic functions. In conclusion, the present study demonstrates that combined microplastic and heavy metal contamination exerts a detrimental effect on soil nutrient availability, resulting in alterations to soil microbial community composition and function. Furthermore, this study shows that these contaminants can inhibit plant growth and heavy metal uptake. The findings provide a valuable contribution to the existing body of knowledge on the ecotoxicological impacts of microplastic–heavy metal composite pollution in terrestrial ecosystems.